DESIGN OPTIMIZATION OF TWO SYNCHRONOUS RELUCTANCE MACHINE STRUCTURES WITH MAXIMIZED TORQUE AND POWER FACTOR - Tahi, Slimane; Ibtiouen, Rachid; Bounekhla, Mhamed (Progress in electromagnetics research. Research B, 2011)
The subject of this article is to optimize the design of synchronous reluctance machines with massive rotor and multi-flux barrier rotor. The optimization procedure, which aims to improve simultaneously the machines' torque and the power factor, uses the cyclic coordinate method coupled with the magnetostatic finite-element (FE) field solutions. The optimization results regarding these two types of machines, which provide the optimized rotor geometrical dimensions and the influence of the current angle, are discussed.